Religion or halakha : the philosophy of Rabbi Joseph B. Soloveitchik - Schwartz, Dov. (Supplements to The Journal of Jewish Thought and Philosophy, 2007)
Joseph B. Soloveitchik's philosophy plays a significant role in twentieth century Jewish thought. This book focuses on the first stages of Soloveitchik's philosophy, through a systematic and detailed discussion of his essay Halakhic Man. Schwartz analyzes this essay at three main levels: first, he considers its complex writing style and relates it to Soloveitchik's aims in the writing of this work. Second, the author compares Halakhic Man to other contemporary writings of Soloveitchik. Third, he lays out the essay's philosophical background. Through this analysis, Schwartz successfully exposes hidden layers in Halakhic Man, which may not be immediately evident. This book is also available in paperback.